2019
DOI: 10.3390/cryst9100512
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Optical, and Thermal Properties of 9, 10-Diphenylanthracene Crystals

Abstract: 9,10-diphenylanthracene (DPA) single crystal is a promising scintillator material for fast-neutron detection. Two centimetre-sized polymorph crystals of DPA were grown by melting and solution methods (DPA-Melt and DPA-Solution, respectively), and characterised by single-crystal X-ray diffraction, Raman spectroscopy, Fourier-transform infrared spectroscopy, fluorescence spectroscopy, UV-Vis absorbance spectroscopy, and thermogravimetric/differential scanning calorimetry. The DPA-Melt crystal possessed a P21/n s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
2
1
Order By: Relevance
“…Polarized transmission images of the same view showed that these domains had different behaviors of the transmittance, which changed by rotating the polarizer (Figure S27, bottom row). Liu and co-workers reported that two different shapes of the fluorescence spectrum exist for DPA crystals depending on their different crystal structures . The two fluorescence spectra that we observed are probably due to such polymorphism of the DPA crystal, although peak wavelengths are not exactly matched to their values.…”
Section: Methodscontrasting
confidence: 55%
See 1 more Smart Citation
“…Polarized transmission images of the same view showed that these domains had different behaviors of the transmittance, which changed by rotating the polarizer (Figure S27, bottom row). Liu and co-workers reported that two different shapes of the fluorescence spectrum exist for DPA crystals depending on their different crystal structures . The two fluorescence spectra that we observed are probably due to such polymorphism of the DPA crystal, although peak wavelengths are not exactly matched to their values.…”
Section: Methodscontrasting
confidence: 55%
“…Liu and co-workers reported that two different shapes of the fluorescence spectrum exist for DPA crystals depending on their different crystal structures. 34 The two fluorescence spectra that we observed are probably due to such polymorphism of the DPA crystal, although peak wavelengths are not exactly matched to their values. DPA is also known to occasionally exhibit excimer emission in the solid state with peaks around 510 and 540 nm, but its appearance depends strongly on the morphology.…”
Section: Fabrication Of Film Samples By Solutionmentioning
confidence: 59%
“…In order to investigate the role of steric effect in the formation of penetrated dimers of chiral emitters that lead to helix inversion, a phenyl anthracene group was incorporated into the [2,2]paracyclophane skeleton, resulting in the compound R ‐PCPA. As the dihedral angle between the phenyl and anthracene groups in 9,10‐diphenyl anthracene is known to inhibit intermolecular π‐π stacking, [23] it is expected that the crowded aromatics in R ‐PCPA would prevent the formation of a dependent macroscopic chirality effect. The parameter φ of R ‐PCPA is 0.49, with the phenyl rings exhibiting a crowded structure almost perpendicular to the anthracene groups (Figure S18).…”
Section: Resultsmentioning
confidence: 99%